High foliar K and P resorption efficiencies in old‐growth tropical forests growing on nutrient‐poor soils. Issue 13 (14th June 2021) - Urbina, Ifigenia; Grau, Oriol; Sardans, Jordi; Margalef, Olga; Peguero, Guillermo; Asensio, Dolores; LLusià, Joan; Ogaya, Romà; Gargallo‐Garriga, Albert; Van Langenhove, Leandro; Verryckt, Lore T.; Courtois, Elodie A.; et al.
Abstract: Resorption is the active withdrawal of nutrients before leaf abscission. This mechanism represents an important strategy to maintain efficient nutrient cycling; however, resorption is poorly characterized in old‐growth tropical forests growing in nutrient‐poor soils. We investigated nutrient resorption from leaves in 39 tree species in two tropical forests on the Guiana Shield, French Guiana, to investigate whether resorption efficiencies varied with soil nutrient, seasonality, and species traits. The stocks of P in leaves, litter, and soil were low at both sites, indicating potential P limitation of the forests. Accordingly, mean resorption efficiencies were higher for P (35.9%) and potassium (K; 44.6%) than for nitrogen (N; 10.3%). K resorption was higher in the wet (70.2%) than in the dry (41.7%) season. P resorption increased slightly with decreasing total soil P; and N and P resorptions were positively related to their foliar concentrations. We conclude that nutrient resorption is a key plant nutrition strategy in these old‐growth tropical forests, that trees with high foliar nutrient concentration reabsorb more nutrient, and that nutrients resorption in leaves, except P, are quite decoupled from nutrients in the soil. Seasonality and biochemical limitation played a role in the resorption of nutrients in leaves, but species‐specific requirements obscured general tendencies at stand and ecosystem level. Abstract : Resorption is a key plant nutrition strategy in old‐growth tropical forests. Trees with high foliar nutrient concentration reabsorb more nutrients. Nutrients resorption in leaves, except P, are quite decoupled from nutrients in the soil. Seasonality and biochemical limitation played a role in the resorption of nutrients in leaves, but species‐specific requirements obscured general tendencies at stand and ecosystem level.